2016
DOI: 10.1080/10410236.2016.1214217
|View full text |Cite
|
Sign up to set email alerts
|

Lay Epistemology of Breast Cancer Screening Guidelines Among Appalachian Women

Abstract: Recent changes to the U.S. Preventive Services Task Force guidelines for breast cancer screening have contributed to increased patient uncertainty regarding the timing and appropriateness of screening behaviors. To gain insight into the lay epistemology of women regarding breast cancer screening practices, we conducted in-depth, face-to-face interviews with 24 adult women living in a medically underserved Appalachian region. We found that women were unaware of breast cancer screening guidelines (i.e., start ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Cancer knowledge, attitudes, and beliefs influence intention and behavior (36). Few respondents knew the correct age to start mammography screening, probably due to confusion over guidelines (37), whereas many more knew the correct age to being colorectal cancer screening. Attitudes about cancer were, for the most part, negative (e.g., many agreed that cancer is fatal and everything causes cancer).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer knowledge, attitudes, and beliefs influence intention and behavior (36). Few respondents knew the correct age to start mammography screening, probably due to confusion over guidelines (37), whereas many more knew the correct age to being colorectal cancer screening. Attitudes about cancer were, for the most part, negative (e.g., many agreed that cancer is fatal and everything causes cancer).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor is malignant (cancer) if the cells can grow into (invade) surrounding tissues or spread (metastasize) to distant areas of the body. Breast cancer occurs almost entirely in women, but men can get breast cancer, too 21 . Breast cancer is the most common malignancy affecting women worldwide 22 .…”
Section: Fig 2: Recent Cancer Scenario In the Worldmentioning
confidence: 99%
“…For example, Hansen et al found that women who received cervical cancer screening were more likely to be aware of the recommended screening interval [ 14 ]. However, previous studies suggested that knowledge of screening guidelines is low in primary care [ 15 - 17 ]. Considering that primary care physicians play a central role in screening— performing Pap tests, distributing FOBT kits, and referring patients for mammography, as well as educating patients about screening and screening guidelines—it is important to understand if patients’ knowledge of cancer screening guidelines is associated with screening uptake.…”
Section: Introductionmentioning
confidence: 99%